Where to put the kids? Effects of type of non-parental child care on pre-teen skills and risky behavior - Nabanita Datta Gupta; Marianne Simonsen (Institute for the Study of Labor (IZA), 2011)
This paper investigates pre-teenage effects of the choice of type of non-parental child care at age three (preschool relative to more informal family day care). We exploit a Danish panel data child survey merged with administrative records along with a pseudo-experiment that generates variation in the take-up of preschool across municipalities. As outcomes, we consider measures of overall and risky behavior in addition to objective and self-evaluated abilities. We find no strong evidence that one type of non-parental care outperforms the other, though children who have been placed in preschool tend to like school better.
urn:nbn:de:101:1-201107283743
Keywords: J13; 330; child care; skills; risky behaviors; evaluation